PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE 3 PADA MATERI PERDAGANGAN INTERNASIONAL DI SMP BAHRUL MAGHFIROH - Rizal Hisam Afandi; Listyo Yudha Irawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the validity and effectiveness of the interactive learning media Articulate Storyline 3 on international trade material. The method used in this study is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation & Evaluation). The data collection technique was carried out by testing the validity of learning media experts and material experts, as well as conducting a media feasibility test on 8th grade junior high school students. From the results of the media validation, it was obtained that this interactive learning media had an average value of 4.35 and could be interpreted as very feasible, and the results of the material validation had a range of X values ​​> 4.6 with a very feasible category. The results of the feasibility test by students had a score of 93% with a very feasible category. Based on the results of the data processing, it can be concluded that the interactive learning media based on Articullate Storyline 3 on international trade material is categorized as very feasible to use.